Analisis kesulitan implementasi kurikulum merdeka di kelas XI BD di SMK N 1 Bangli - I Komang Agus Hendrawan; Luh Made Dwi Wedayanthi; Kadek Dwi Pebriyanti (BADAN PENERBIT STIEPARI PRESS, 2024)
This research examines the challenges faced in implementing the Merdeka Curriculum within the context of Class XI BD at SMK N 1 Bangli. Using a qualitative descriptive approach, the study engages teachers and students as subjects, employing observation, interviews, and document analysis for data collection. The findings underscore the presence of diverse student characteristics, facility limitations, and a primary emphasis on the development of soft skills as major obstacles. Despite teachers' creative efforts in adopting innovative teaching methodologies, the passive response from students necessitates modifications to lesson plans. Recommendations include facility enhancements, teacher training initiatives, personalized strategies for cultivating soft skills, and vital support from educational institutions and parents.